Large cell neuroendocrine carcinoma of the maxillary sinus on fine needle aspiration cytology: Report of a rare case with a focus on pitfalls in diagnosis. Issue 2 (14th September 2017) - Kawahara, Akihiko; Ono, Takeharu; Sumi, Akiko; Abe, Hideyuki; Takase, Yorihiko; Murata, Kazuya; Yamaguchi, Tomohiko; Naito, Yoshiki; Akiba, Jun
Abstract : Head and neck large cell neuroendocrine carcinoma (LCNEC) is a rare high‐grade malignant tumor with neuroendocrine differentiation. We report a case of LCNEC causing difficulty in cytological diagnosis. A 60‐year‐old man with right‐sided face pain presented with a swelling at the right cheek, and he complained of right nasal obstruction and lacrimation. Preoperative fine‐needle aspiration cytology (FNAC) showed high cellularity, with a moderate number of clusters of tumor cells on an abundant necrotic background. The clusters were arranged in sheet structures with palisading, and were cohesive with overlapping. The tumor cells had comparatively abundant cytoplasm, with conspicuous large, irregular nucleoli with a fine granular chromatin pattern. Mitotic figures were observed easily. On immunocytochemistry using LBC smear, tumor cells were negative for p40. High‐grade carcinoma other than non‐keratinizing squamous cell carcinoma was suggested from these findings on FNAC. The pretreatment histological biopsy sample revealed tumor cells with solid growth pattern, necrotic materials and large polygonal cells with abundant cytoplasm, fine granular chromatin, and conspicuous nucleoli. Head and neck LCNEC with abundant cytoplasm, fine granular chromatin patterns, prominent nucleoli, and necrotic background were very characteristic of LCNEC. If considered carefully, these findings can enable us to exclude the majority of non‐keratinizing squamous cell carcinomas, and FNAC using ancillary technique can be very useful for proper diagnosis.